Estudio de paneles de fibropoliuretano para uso en mamposterías - Albán Clavijo, Blanca Maribel (2012)
The purpose of the present investigation is the manufacture of a panel formed of Fibrocement and rigid polyurethane foam called "Panel of Fibropoliurethane", and its possible use as masonry in general.   To reach the indicated premise, this new product in the first instance must be analyzed in the laboratory, faced with loads, these results will be the indicators that will qualify the manufacturing process developed, as homogeneous, and will provide its specific characterization.